Real and Imaginary Travels 16th-18th centuries - Rémi Vuillemin (Presses universitaires de Strasbourg, 2015)
Whether real or imaginary, travel stands as a paradigm for the circulation and the production of beliefs and ideas, and can have as much to do with education or spirituality as with utopian politics or the development of trade. Ten European researchers focus - in English and in French - on real or fictional, experienced or narrated journeys, from the Renaissance to the Enlightenment, a period that witnessed the intellectual construction of modern Europe, and the rise to prominence of England and the United Kingdom.